Active citizenship, companies and purpose: the perspective of Spanish society. - Ruiz-Mora, Isabel María; Barroso, María-Belén; Álvarez-Nobell, Alejandro (My University, 2023)
There is a debate about the need to reframe the current economic system (Canvas, 2022) towards one that is more inclusive and sustainable, providing an opportunity to take action and move towards the 2030 Agenda. In this emerging scenario, citizenship assumes an active and pollinating role (Fernández & Díaz, 2020; Theben et al., 2021), encouraging organizations to rethink their purpose, measuring beyond the financial dimensions. Previous studies have shown that companies that follow this approach have a positive impact on business, society and the planet. Purpose-driven companies are aligned with the triple impact (Elkington, 2020;) and stakeholder capitalism (Freeman, 1984). The research was designed with the aim of analyzing Spanish society's perception of the capitalist system; of purpose-driven companies; and the role of citizenship. Following a mixed approach, the survey technique was chosen, consisting of 25 closed questions following the three axes of the research: current economic system; purpose-driven companies and active citizenship. The fieldwork was carried out in the last quarter of 2022 (1004 valid responses from a representative sample. There is a clear need for transformation and the realization of a general crisis in the way we organize ourselves as a society. 55.6% of Spanish citizens do not approve of the current capitalist system and 77% believe that the current system should undergo a major transformation, at the very least. The lack of knowledge about purpose-driven companies is the same throughout Spain. However, it can be observed that there are people who have heard of them and who have had dealings with this type of company. In line with this lack of knowledge, a certain generalized distrust of the role of these companies is also observed. 64.5% of people say that they make small decisions in their daily lives to take care of the planet's resources, but 34.2% are not entirely satisfied with their own actions to impact the planet.
Keywords: Economía social; Valores sociales; Active citizenship; Purpose-driven companies; Triple Bottom Line; 2030 Agenda; Business; Spain; Ciudadanía activa; Empresas con propósito; Triple impacto; Agenda 2030; Negocios; España; Bcorps